Principles and methods of teaching - Lardizabal, Amparo S.; Bustos, Alicia S.; Bucu, Luz C.; Tanggo Maura G. (Quezon City : Phoenix, 1995)
This book is intended primarily for beginning teachers who need to have a strong foundation and through grasp of the teaching-learning theories and principles. It is also intended for teachers who are already in the service and who want to improve their competency and to update themselves on current6 trends, techniques, and approaches in the teaching profession.
1. The Teacher and his profession -- 2. Teaching and learning principles and methodology -- 3. Planning lessons -- 4. Types of lessons -- 5. Time-tested methods -- 6. Improved instructional practices and discussion procedures -- 7. Multisensory aids to teaching -- 8. Aids to effective teaching: the recitation, assignment, and art of questioning -- 9. Classroom management -- 10. Assessing instructional outcomes.
Includes bibliographical references and index.
Keywords: TEACHING